Co-Digestion of Vinasse Waste and Tofu Liquid Waste to Increase Biogas Production - Iqbal Syaichurrozi (Eksergi, 2015)
The purpose of this study was to increase biogas production using co-digestion concept. Vinasse Waste (VW) containing high COD and low total Nitrogen content was mixtured with Tofu Liquid Waste (TLW) containing low COD and high total Nitrogen. Substrates were varied with volume ratio of VW:TLW of 100:0, 20:80, 0:100. Total volume of substrates was 250 mL. Anaerobic digesters were operated at room temperatur. After fermentation, biogas total volume of variables of 100:0, 20:80, 0:100 was 88.5; 125.5; 41.5 mL. Initial pH for all variables was 7.0. At the end of fermentation, pH substrates became 3.9; 5.1; 6.8 for variables of 100:0, 20:80, 0:100 respectively.